The hypermobility spectrum in rugby union players, netballers and dancers: implications for injury and performance - Ross Armstrong (Kazimierz Wielki University, 2018)
Objectives: Hypermobility has been associated with injury and performance and a new hypermobility framework has been introduced. This study aimed to report the prevalence of localised joint hypermobility, generalised joint hypermobility (GJH), peripheral joint hypermobility and hypermobility Ehlers-Danlos type in female rugby players, male rugby players, female netball players, female dancers, male and female controls. Methods: This study determined joint hypermobility via the Beighton score and the associated criteria of the hypermobility spectrum in 378 participants. Results: Localised joint hypermobility ranged from 61.11% (netballers), 57.33% (female rugby), 48.15% (male controls), 46.30% (male rugby), 38.33% (female controls) to 28.57% (female dancers). Significant differences existed for Beighton scores (p